Architectural impacts of in-situ resource utilization production of oxygen for use as propellant in a Mars ascent vehicle. Issue 1 (1st May 2022) - Krenn, A; Trent, D; Sanders, G; Hoffman, S; Chai, P; Hinterman, E
Abstract: NASA is in the processes of evaluating various architectures that may support human missions to Mars. A multitude of concepts are being traded and associated sensitivities are being analyzed. Among these trades, several options for Mars Ascent Vehicle (MAV) propellant supply are being considered. Due to mass constraints on the Mars descent system and the in-space transportation system, landing a fully fueled MAV, that can launch humans from the surface of Mars, presents significant integrated architecture challenges. Consequently, MAV propellant must either be pre-positioned and transferred across the surface robotically or made on the surface via In-Situ Resource Utilization (ISRU) techniques. In each case, there are implications to the number of architecture elements, total system mass, power requirements, complexity of operations, and required technology developments. An analysis that compares an ISRU point solution to a similar point solution that pre-positions and transfers propellant is detailed.